Fabrication of Hexagonal Boron Nitride Nanosheets by Using a Simple Thermal Exfoliation Process. Issue 3 (22nd February 2016) - Ko, Wen‐Yin; Chen, Cheng‐Yu; Chen, Wei‐Hung; Lin, Kuan‐Jiuh
Abstract: A simple and inexpensive method to exfoliate boron nitride powder to form boron nitride nanosheets (BNNSs) with few layers was achieved by using a physically thermal process. The obtained BNNSs were characterized by transmission electron microscopy (TEM), scanning electron microscopy (SEM), atomic force microscopy (AFM), X‐ray diffraction (XRD), X‐ray photoelectron spectroscopy (XPS), IR spectroscopy, and Raman spectroscopy. The size distribution of the sheets and average sheet size is in the range of 80–380 nm and 200±62 nm, respectively, and the pure phase h‐BN products were confirmed. XPS result showed the B/N atomic ratio to be 0.99. In addition, the BNNSs can well disperse in aqueous solution to form a cloudy suspension and importantly, can remain suspended for 1 month without precipitate, which would have good potential in a wide range of applications. Abstract : A simple and inexpensive physically thermal process to exfoliate boron nitride powder to form boron nitride nanosheets (BNNSs) with only few layers, average sheet size of around 230 nm and pure phase h‐BN crystalline, was achieved. Importantly, the BNNSs can well disperse in aqueous solution to form a cloudy suspension and importantly, can remain suspended for 1 month without precipitate.